2020
DOI: 10.1101/2020.09.11.292631
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A key linear epitope for a potent neutralizing antibody to SARS-CoV-2 S-RBD

Abstract: The spread of SARS-CoV-2 confers a serious threat to the public health without effective intervention strategies1–3. Its variant carrying mutated Spike (S) protein D614G (SD614G) has become the most prevalent form in the current global pandemic4,5. We have identified a large panel of potential neutralizing antibodies (NAbs) targeting the receptor-binding domain (RBD) of SARS-CoV-2 S6. Here, we focused on the top 20 potential NAbs for the mechanism study. Of them, the top 4 NAbs could individually neutralize bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…Other investigators ( 81 ) using in vitro antibody selection identified a change at amino acid site S151 in the N-terminal domain, and we found mutations S151N and S151I in our patient samples. We also note that two variant amino acids (Gly446Val and Phe456Leu) that we identified were located in a linear epitope found to be critical for a neutralizing monoclonal antibody described recently by Li et al ( 82 ).…”
Section: Discussionsupporting
confidence: 70%
“…Other investigators ( 81 ) using in vitro antibody selection identified a change at amino acid site S151 in the N-terminal domain, and we found mutations S151N and S151I in our patient samples. We also note that two variant amino acids (Gly446Val and Phe456Leu) that we identified were located in a linear epitope found to be critical for a neutralizing monoclonal antibody described recently by Li et al ( 82 ).…”
Section: Discussionsupporting
confidence: 70%
“…Other investigators (86) using in vitro antibody selection identified a change at amino acid site S151 in the N-terminal domain, and we found mutations S151N and S151I in our patient samples. We also note that two variant amino acids (Gly446Val and Phe456Leu) we identified are located in a linear epitope found to be critical for a neutralizing monoclonal antibody described recently by Li et al (87).…”
Section: Discussionsupporting
confidence: 69%
“…Experimental data pertaining to neutralization of S(G614) and S(D614) pseudoviruses have been reported in abundance. The majority of experiments demonstrate similar neutralization of both S(D614) and S(G614) PVs by antibodies or patient antisera directed against one or the other S protein variant [ 28 , 35 , 51 , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] ], while in some cases S(G614) exhibited greater susceptibility to neutralization [ 51 , 57 ]. Similar neutralization or greater susceptibility of the S(G614) variant have been reproduced with live SARS-CoV-2 as well [ 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%